Numerical Study on the Influence of Distributing Chamber Volume on Metallurgical Effects in Two-Strand Induction Heating Tundish - Bin Yang; Anyuan Deng; Xiaolei Kang; Pengfei Duan; Engang Wang (Metals, 2022)
Reducing the volume of distributing chamber by shortening its width is one of the ways to obtain good metallurgical effects for a large two-strand induction heating tundish. A multi-field coupling numerical model was established to figure out the effect of distributing chamber volume on the flow field, temperature field of molten steel, and removal of inclusions. Three tundishes with distributing chamber widths of 1.216 m (tundish A), 0.838 m (tundish B), and 0.606 m (tundish C) were modeled. The results indicated that reducing the width of the distributing chamber from 1.216 m to 0.838 and 0.606 m could improve the fastest heating rate from 0.4 K/min to 0.6 and 0.8 K/min and reduce the energy consumption from 476 kWh to 444 and 434 kWh. The temperature fluctuation of molten steel in the distributing chamber rose with the decrease in distributing chamber volume during the continuous casting process. Besides, tundish B performs the best temperature uniformity. The flow field in the distributing chamber was no longer symmetrical, and a short-circuit flow appeared when the width was reduced to 0.606 m. As a result, the floating ratio and removal ratio of inclusions decreased and the ratio of inclusions flowing into the mold sharply increased in tundish C. When the width was reduced from 1.216 to 0.838 m, the floating ratio of inclusions had little change and the removal ratio increased slightly. The floating efficiency increased with the decrease in the volume of distributing chamber, and the removal efficiency is the highest in tundish B. Taken together, tundish B should be adopted.